Oxidative Stress and Its Correction in Patients with Severe Concomitant Injury - V. M. Kapitonov; D. A. Ostapchenko (Общая реаниматология, 2010)
In severe concomitant injury, there is evidently activated formation of free radicals with a further increase in the rate of lipid per-oxidation and with simultaneous depletion of antioxidant system activity. The administration of the traditional doses of antioxi-dants is ineffective. Higher-dose antioxidant therapy and use of novel agents can cause a considerable reduction in the rate of free radical processes and improve the results of treatment. Key words: oxidative stress, lipid peroxidation, antioxidants, lactoferrin.